Wie handelt Gott durch die Sakramente?: spirituelle und theologische Erkundungen - Körner, Bernhard (Zeitschrift für katholische Theologie, 2006)
Modernity thinks of God as more and more remote. Consequently, the biblical speech of the acts of God becomes problematic. ‚This article argues for an understanding of the sacraments as spaces of encounter between God and human beings. Such an understanding allows for a theologically responsible discourse about the acts of God and opens up an understanding of the importance of personal encounters and their relevance for the relationship between humans and God.